Camtasia Studio-Based Arabic Learning Video Design for Arabic Language Education Students - Ahkas, Akmal Walad; Zulheddi, Zulheddi; Ardiansyah, Muhammad; Al-‘Anazy, Majid Dakhil (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
This research aims to develop Camtasia studio-based learning video products for Arabic Language Education students, focusing on the stages of learning video design and media feasibility analysis and Camtasia Studio-based learning video materials. This research was conducted to provide alternative learning media that can be prepared by lecturers so that students are not bored and enthusiastic about attending lectures. This research used the Research and Development (R&D) method with the ADDIE model covering 5 stages, namely, (a) analyzing needs so that video products that need to be developed can be found; (b) designing video products as required; (c) conduct testing and development of video products; (d) use video products and product trials and (e) evaluate and assess each step of the activities and video products that have been created by specifications.  This research involves media experts and material experts as well as 30 students who will test the video product. The results of the trial of Camtasia studio-based learning media products averaged 86% and 92% of material expert validation scores so that they got the "feasible/valid" category. The results of product trials (limited product trials) received an average score of 80% and 93% with the category "very valid". So, it can be concluded that Camtasia studio-based learning media is feasible and can be used for lecturers and students of Arabic Language Education.